(untitled) (The International Journal for Scientific Research, 2024)
This study aims to establish the foundation for the topic "Doctrinal Dialogue in Surah Al-An’am: An Integrative Analysis of Ibrahim’s Dialogues," considering the diversity of contemporary Islamic preaching methods and approaches. The study seeks to highlight the significance of doctrinal dialogue in Quranic storytelling, focusing on the analysis of Ibrahim’s dialogues in Surah Al-An’am from doctrinal perspectives. It explores how these dialogues elucidate doctrinal truths through a compelling dialectical approach, thereby enhancing their effectiveness as a tool for dawah and providing a valuable model for contemporary dawah discourse. To achieve these objectives, an inductive, descriptive, and analytical methodology was followed, adhering to established research methods. The research focuses on providing a comprehensive answer to the central question: How can a preacher benefit from Quranic dialogues in enhancing their dawah and elucidating Islamic doctrines in an engaging and effective manner?